On the Vowel Epenthesis and Epithesis in Turkish Texts in the Manuscripts of Lithuanian Tatars - Durgut, Hüseyin (Lietuvos istorijos studijos, 2023)
Adding a vowel that is not in the original of a word to that word for various reasons is called vowel derivation. There is no morphological reason for vowel derivation and it aims to facilitate the pronunciation. There are three types of vowel derivation: at the beginning of the word, within the word and at the end of the word. The derivation of vowels at the beginning of a word in Turkish is not seen much in standard Turkish and is more common in dialects. Vowel epenthesis is a common phonetic event in standard Turkish. This phonetic event is encountered both in borrowed words and in words of Turkish origin. One of the reasons for the vowel epenthesis in Turkish is to make the borrowed words that do not fit the syllable structure of Turkish fit the syllable this structure and thus to eliminate the difficulty of pronunciation in the borrowed words. As it is known, only some consonant pairs can be found together at the end of words of Turkish origin. For this reason, in words borrowed with consonant pairs that are not suitable for the syllabic structure of Turkish, we come across vowel derivations within the word. This vowel derivation, which first appeared in the spoken language, can also pass into the standard language over time. The vowel epenthesis can also be seen in some Turkish origin words in order to add strength to the meaning. In Turkish, vowel epithesis is not as common as vowel epenthesis. The vowel epithesis is mostly seen in dialects and there are very few examples in standard language. The vowel epithesis is a phonetic event that is more common in some Turkic languages than in Türkiye Turkish. The derivation of vowel at the end of the word, especially seen in borrowed words, provides ease of pronunciation in words of foreign origin that do not fit the sound system of the Turkish language. The vowel epithesis occurs in borrowed words containing consonant pairs that are not suitable for the syllable structure of Turkish, as well as in borrowed words with twin consonants at the end of the word. It is seen that examples of vowel epithesis in Turkish texts found in manuscripts of Lithuanian Tatars are more common than in Türkiye Turkish. In particular, the Miraj text and some poems belonging to the Old Anatolian Turkish period, which are among the manuscripts in the “kitab” type, provide us with a rich material on this subject. In these texts, examples of vowel epenthesis and epithesis in borrowed words from Arabic and Persian are used in pairs in an interesting way. In other words, we see that the same borrowed word is used both with vowel epenthesis and epithesis. In this study, events of vowel epenthesis and epithesis in Turkish texts found in manuscripts of Lithuanian Tatars are examined and the reasons for the higher incidence of vowel epithesis in these texts are discussed.